Persepsi dan Dampak Pembelajaran Berbasis Masalah pada Mahasiswa Peserta Program Merdeka Belajar Kampus Merdeka Asistensi Mengajar - Rini, Hapsari Puspita; Natalia Susanti, Ruth (Indo-MathEdu Intellectuals Journal, 2024)
The MBKM Teaching Assistance Program is implemented based on the principle of problem-based learning where students involved in this program will conduct learning in designated educational units to engage in the teaching and learning process and help solve some of the problems encountered. The purpose of this study is to explore the perceptions of students who have participated in the program to find out how far the achievements and benefits obtained through this program so that later it can be a recommendation for improving the implementation of the next program. This research uses a descriptive qualitative method where the data collection process is carried out through interviews with a total of three respondents. The respondents selected were students participating in the MBKM Teaching Assistance program who underwent the internship process in different educational units The results of this study are that students participating in the program feel the benefits of increasing knowledge and skills both directly related to lecture science and skills in other forms such as self-adjustment, self-management, collaboration, and reflective thinking